Acute diverticulitis complicated by massive lower gastrointestinal bleeding: a rare diagnostic challenge. Issue 9 (7th September 2022) - Hutchison, Ann; Lee, Yongjin F; Eggenberger, John; Cleary, Robert
Abstract : A man in his 70s presented with acute sigmoid diverticulitis complicated by a large pericolonic abscess abutting the left rectus abdominis muscle. He was admitted for non-operative management. On hospital day 2, he developed haemorrhagic shock from profuse haematochezia. Colonoscopy was not advisable in the setting of acute complicated diverticulitis. Placement of a percutaneous drain into the abscess cavity returned bright red blood, which was concerning for erosion of the diverticular abscess into the left inferior epigastric artery. An urgent diagnostic angiogram showed hyperaemia enveloping the abscess cavity. Haemostasis was achieved by angioembolisation of the left inferior epigastric artery. The patient did well and was discharged with a course of antibiotics in anticipation of an elective sigmoidectomy.